Analisis Hukum Islam tentang Penyelenggaraan Shalat Jumat dan Ibadah di Masjid dalam Situasi Tanggap Darurat Covid-19 - Imam Khoirul Ulumuddin; A. Saiful Aziz; Tri Handayani; Akhmad Nurasikin (Universitas Wahid Hasyim Semarang, 2022)
AbstractThe year 2020 is a year that worries people all over the world with the outbreak of the Corona Virus Disease 2019 (COVID-19), and Indonesia is no exception. The rapid spread of the Corona Virus (Covid-19) has caused various problems in all aspects of life, including the issue of holding public worship. This study aims to analyze the Central Java MUI Tausiah Number: 02/DP-P.XIII/T/IV/2020 related to the implementation of Friday prayers and worship at the mosque in the Covid-19 emergency response situation. This research is a type of literary research (library research). , using a qualitative method with a descriptive approach to the analysis of Islamic law, namely describing and studying the problem using the study of Islamic law, then analyzing it. The results of the study conclude that the Central Java MUI Tausiah Number: 02/DP-P.XIII/T/IV/2020 is not only based on naqli and aqli arguments, but also through several considerations, including an appeal from WHO which is a world health organization and also the decision of the Regional Government through its Covid Cluster, so that in distributing tausiah, it has been carefully discussed and not arbitrarily circulated. Differences of opinion in accepting decisions are sunnatullah that cannot be avoided, so there needs to be a wise attitude in dealing with this.Keywords: Friday prayer; Worship in the Mosque; Covid-19 EmergencyAbstrakTahun 2020 merupakan tahun yang mengkawatirkan masyarakat seluruh dunia dengan adanya wabah Corona Virus Disease 2019 (COVID-19), tak terkecuali di Indonesia. Penyebaran Virus Corona (Covid-19) ini yang begitu cepat menimbulkan berbagai permasalahan di segala aspek kehidupan, tak terkecuali dalam masalah penyelenggaraan ibadah di muka publik. Penelitian ini bertujuan untuk menganalisis Tausiah MUI Jawa Tengah Nomor: 02/DP-P.XIII/T/IV/2020 terkait penyelengaraan shalat jumat dan ibadah di masjid dalam situasi tanggap darurat covid-19, Penelitian ini merupakan Jenis Penelitian literer (library research), menggunakan metode kualitatif dengan pendekatan deskriptif analisis hukum Islam, yakni mendeskripsikan dan mengkaji permasalah menggunakan kajian hukum Islam, kemudian menganalisisnya. Hasil penelitian menyimpulkan bahwasannya Tausiah MUI Jawa Tengah Nomor: 02/DP-P.XIII/T/IV/2020 tidak hanya berdasarkan dalil-dalil naqli dan aqli, dan juga melalui beberapa pertimbangan, diantarannya adalah himbauhan dari WHO yang merupakan organisasi kesehatan dunia dan juga keputusan Pemerintah Daerah melalui Gugus Covidnya, sehingga dalam mengedarkan tausiah memang sudah digodok secara matang dan tidak sembarangan untuk diedarkan. Perbedaan pendapat dalam menerima keputusan memang merupakan sunatullah yang tidak bisa dihindari, sehingga perlu adanya sikap yang bijaksana dalam menyikapi hal tersebut.